Primary skin irritation study of calcium alginate film - Gutierrez, Oscar Jr.; Calderon, Carlito J.
Calcium alginate film is a new product developed by the Philippine Textile Research Institute, Department of Science and Technology that is derived from indigenous seaweeds. It may be used to protect non-intact skin and perhaps promote faster healing. In the present study, test samples of calcium alginate film were tested in BFAD:JW (Japanese White) rabbit following the procedure for Primary skin Irritation Test for Biomaterials, based on the published work of Draize, J.H., Woodard, G., and Calvery, H.O. in 1944. The aim of the study was to evaluate the irritating property of calcium alginate film on intact and abraded skin of rabbit. The result of the study showed that calcium alginate film has a Primary Irritation Index of 0.027 which categorizes it as non-irritant substance.(Author)
BFAD Laboratory Information Bulletin, 1997 3 (1) pages 1-3
Keywords: Alginates -- adverse effects; Skin Irritancy Tests